Insights into preventing female genital mutilation/cutting in Sri Lanka: a qualitative interpretative study - Dawson, Angela (Reprod Health, 2021)
BACKGROUND: FGM/C is a cultural practice associated with adverse health outcomes that involves the partial or complete removal of the external female genitalia or injury to the genitalia. FGM/C is a form of violence against women and girls. There are no laws that specifically outlaw FGM/C in Sri Lanka and no national prevalence data. There is a lack of evidence about this practice to inform prevention efforts required to achieve the Sustainable Development Goal (SDG) target 5.3.2, which focuses on the elimination of all harmful practices, including FGM/C. METHODS: We undertook a qualitative interpretative study to explore the knowledge and perceptions of community members, religious leaders and professionals from the health, legal and community work sectors in five districts across Sri Lanka. We aimed to identify strategies to end this practice. RESULTS: Two-hundred-and twenty-one people participated in focus group discussions and key informant interviews. A template analysis identified five top-level themes: Providers, procedures and associated rituals; demand and decision-making; the role of religion; perceived benefits and adverse outcomes; ways forward for prevention. CONCLUSIONS: This study delivered detailed knowledge of FGM/C related beliefs, perceptions and practitioners and provided opportunities to develop an integrated programming strategy that incorporates interventions across three levels of prevention.